2021
DOI: 10.3390/cancers13184732
|View full text |Cite
|
Sign up to set email alerts
|

Senescence in HBV-, HCV- and NAFLD- Mediated Hepatocellular Carcinoma and Senotherapeutics: Current Evidence and Future Perspective

Abstract: Cell senescence constitutes a physiological process that serves as protection from malignant transformation of cells. However, recent scientific discoveries also identify cell senescence as pivotal in hepatocellular cancer (HCC) biology. The review herein aimed to accumulate evidence on senescence as a mediator of HCC occurrence in hepatitis B (HBV), C (HCV) virus infections, and non-alcoholic fatty liver disease (NAFLD). In HBV infection, the carcinogenic HBV X protein frequently mutates during chronic infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 113 publications
(146 reference statements)
0
13
0
Order By: Relevance
“…26 Even though cell senescence is a tumor suppressor mechanism, growing evidence suggests that senescent cells can contribute to cancer including HCC due to the secretion of senescence-associated secretory phenotype that promotes tumor progression. 42 Our study showing that senescence markers were elevated in response to CD-HFD and this effect was reduced in both Ripk3 -/- and Mlkl -/- mice suggests a possible crosstalk between necroptosis and cell senescence. Ripk3 -/- mice showed a sex-specific response in cell senescence inhibition whereas Mlkl -/- mice did not show such an effect.…”
Section: Discussionmentioning
confidence: 67%
“…26 Even though cell senescence is a tumor suppressor mechanism, growing evidence suggests that senescent cells can contribute to cancer including HCC due to the secretion of senescence-associated secretory phenotype that promotes tumor progression. 42 Our study showing that senescence markers were elevated in response to CD-HFD and this effect was reduced in both Ripk3 -/- and Mlkl -/- mice suggests a possible crosstalk between necroptosis and cell senescence. Ripk3 -/- mice showed a sex-specific response in cell senescence inhibition whereas Mlkl -/- mice did not show such an effect.…”
Section: Discussionmentioning
confidence: 67%
“…Additionally, CD8 + T cells isolated from peripheral blood of HCV-infected subjects show higher levels of DNA damage and hypophosphorylated signal transducer and activator of transcription 1 (STAT1) and STAT5 in response to IL-6 or IL-2 stimulation, respectively ( 202 ). Altogether, these data suggest that chronic HCV infection results in cellular senescence, and since these senescent cells are non-functional, they may predispose HCV-infected individuals to HCC ( 203 ).…”
Section: Drivers Of Immunosenescence and Atherosclerosismentioning
confidence: 98%
“…Several in-depth studies of patients with HCC have established associations between particular microbiome compositions and the development of HCC. For example, genera, such as Bacteroides , Phascolarctobacterium , Enterococcus , Streptococcus , Gemella , Bilophila, are increased in patients with HCC from NAFLD and cirrhosis compared to healthy controls [ 43 ]. On the contrary, Akkermansia , Bifidobacterium , Dialister , and Collinsella were found to be downregulated in these patients [ 43 ].…”
Section: Role Of the Microbiome On Inflammatory Processes In Hccmentioning
confidence: 99%
“…For example, genera, such as Bacteroides , Phascolarctobacterium , Enterococcus , Streptococcus , Gemella , Bilophila, are increased in patients with HCC from NAFLD and cirrhosis compared to healthy controls [ 43 ]. On the contrary, Akkermansia , Bifidobacterium , Dialister , and Collinsella were found to be downregulated in these patients [ 43 ]. Other studies pertaining to cirrhosis mediated HCC have identified genera, such as Klebsiella , Haemophilus, Escherichia - Shigella , Proteus , Subdoligranulum , Prevotella 2 , Barnesiella to be upregulated in patients with HCC, whereas Alistipes, Phascolarctobacterium, Rumnocccus, Buchnera , Megamonas , Lachnospira , and Eubacterumventriosum are downregulated [ 35 , 44 ].…”
Section: Role Of the Microbiome On Inflammatory Processes In Hccmentioning
confidence: 99%
See 1 more Smart Citation